PEGylated DOX-coated nano graphene oxide as pH-responsive multifunctional nanocarrier for targeted drug delivery. (14th September 2021) - Ma, Kun; Li, Wenzhe; Zhu, Guang; Chi, Hao; Yin, Yalin; Li, Yijing; Zong, Yan; Guo, Zhaoming; Wang, Li; Xu, Weiping; Cui, Changhao; Zhou, Huiwei; et al.
Abstract: Nano graphene oxide (NGO) has high drug-loading capacity due to its huge surface area. However, the limited stability and the poor biocompatibility of NGO hampered its application as drug delivery carrier under physiological conditions. Thereby, a new strategy of using chemical conjugation on NGO with hydrophilic polymers was adopted but currently was too complicated, low yield and costly. In this study, doxorubicin-hyd-PEG-folic acid (DOX-hyd-PEG-FA) polymers were coated on the surface of NGO via π–π stocking and the hydrophobic effect between DOX and NGO. With the PEG shell protection, the biocompatibility of NGO was significantly improved. The drug-loading capacity of nanoparticles was more than 100%. FA ligands on the nanoparticle could guide the nanoparticles actively targeting to tumour cells. The hydrazone bond between DOX and PEG was decomposed spontaneously in the weakly acidic environment, which made PEG layer dissociated from NGO. Furthermore, DOX was easily protonized at low pH conditions, which weakened the interaction between DOX and NGO. Thus, DOX could be released rapidly from the nanoparticles in tumour cells. In summary, NGO@DOX-hyd-PEG-FA is an easy-prepared nanoparticle with excellent biocompatibility, high pH-sensitivity and active tumour targeting. Therefore, it is a promising multifunctional nanocarrier effective for targeted drug delivery.